2000
DOI: 10.1097/00006982-200003000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Triamcinolone Acetonide in Exudative Age-Related Macular Degeneration

Abstract: Indocyanine green angiography-guided laser treatment may improve or stabilize visual acuity in some eyes with O-CNV. The best outcome is seen in eyes with presumed parapapillary CNV, probably made up of choroidal telangiectases in many cases. The type and location of the presumed CNV influence prognosis after laser treatment considerably. A randomized, controlled clinical study appears necessary to investigate the efficacy of ICGA-guided laser treatment in different types of presumed CNV. The inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
194
3
18

Year Published

2001
2001
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(228 citation statements)
references
References 1 publication
13
194
3
18
Order By: Relevance
“…These adverse effects were particularly evident with the highest dose (50 l, 0.75 nmol/ l), indicating that the volume and concentration of DS135 needs to be further adjusted. Although the cellular infiltration could be minimized by IV use of certain amounts of antiinflammatory drugs (Danis et al, 2000;Flores-Aguilar et al, 1997;Shen et al, 2000), our results may also imply that the undesired side effects of DS135 are associated with the biochemical structure of PS-oligo (Black et al, 1994;Dvorchik and Marquis, 2000). It has been reported that chimeric oligonucleotides consisting of a mixed phosphodiester-phosphorothioate backbone and having 2-methoxyrobonucleotides modification, dramatically eliminated the side effects of PS-oligos but retained the effective potency in the central nerve system (Ho et al, 1998).…”
Section: Ps-oligo In the Retina Of Rhesus Monkeymentioning
confidence: 81%
“…These adverse effects were particularly evident with the highest dose (50 l, 0.75 nmol/ l), indicating that the volume and concentration of DS135 needs to be further adjusted. Although the cellular infiltration could be minimized by IV use of certain amounts of antiinflammatory drugs (Danis et al, 2000;Flores-Aguilar et al, 1997;Shen et al, 2000), our results may also imply that the undesired side effects of DS135 are associated with the biochemical structure of PS-oligo (Black et al, 1994;Dvorchik and Marquis, 2000). It has been reported that chimeric oligonucleotides consisting of a mixed phosphodiester-phosphorothioate backbone and having 2-methoxyrobonucleotides modification, dramatically eliminated the side effects of PS-oligos but retained the effective potency in the central nerve system (Ho et al, 1998).…”
Section: Ps-oligo In the Retina Of Rhesus Monkeymentioning
confidence: 81%
“…Intravitreal triamcinolone acetonide has increasingly been used in previous studies for treatment of intraocular proliferative, oedematous, and neovascular diseases, such as diffuse diabetic macular oedema, [1][2][3] proliferative diabetic retinopathy, 4 neovascular glaucoma, 5 central retinal vein occlusion, [6][7][8] proliferative vitreoretinopathy, 9 chronic pre-phthisical ocular hypotony, 10 chronic uveitis, [11][12][13][14][15] persistent pseudophakic cystoid macular oedema, [16][17][18] exudative age-related macular degeneration, [19][20][21][22][23][24][25] cystoid macular oedema due to retinitis pigmentosa, 26 ischaemic ophthalmopathy, 27 sympathetic ophthalmia, 28 idiopathic juxtafoveal telangiectasis, 29 as visualization aid during pars plana vitrectomy, 30 and in other clinical situations. [31][32][33][34][35][36] In aqueous humour and in silicone oil, respectively, triamcinolone acetonide has been found up to 1.5 years and up to 8 months, respectively, after the intravitreal injection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intravitreal injections of triamcinolone acetonide have increasingly been used as a treatment for these diseases such as exudative age-related macular degeneration, [1][2][3][4][5][6][7][8] diffuse diabetic macular oedema, [6][7][8][9][10][11] central retinal vein occlusion, 12,13 persistent pseudophakic cystoid macular oedema, proliferative diabetic retinopathy, 14 proliferative vitreoretinopathy, 15 iris neovascularisation, 16 chronic prephthisical ocular hypotony, 17 chronic uveitis, [18][19][20][21] and neovascular glaucoma. 22 Complications and side-effects of the intravitreal injection of triamcinolone acetonide include secondary ocular hypertension developing in about 50% of the eyes injected and leading to high intraocular pressure up to 60 mmHg with the need for antiglaucomatous filtering surgery in about 1% of the eyes; 23 infectious endophthalmitis in less than 1% of the eyes, if the injection was performed under sterile criteria in the operation room; and, because of the cataractogenic effect of steroids, a cataract that has eventually to undergo surgery.…”
Section: Introductionmentioning
confidence: 99%